Hepatitis B virus serology : eight years of laboratory data in retrospect - Sim, John. Gray. Malcolm (My University, 1993)
An analysis of 39,774 specimen records of diagnostic screening for hepatitis B virus (HBV), consisting of HBV surface antigen (HBsAg), antibody to surface antigen (anti- HBs) and antibody to HBV core antigen (anti-HBc) was performed. Specimens representative of all possible result combinations for these primary markers were found in the dataset and were investigated further by studying the distribution of extended marker frequencies within the groups defined by the primary marker combinations in an attempt to reconcile the patterns observed with standard profiles of HBV serology. The extended markers consisted of HBV e antigen (HBeAg), antibody to HBeAg (anti- HBe) and anti-HBc IgM. Unusual patterns of serological results which were identified were investigated further for the presence of HBsAg/anti-HBs immune complexing by acid dissociation techniques, and for the low level HBV chronic carrier state by polymerase chain reaction (PCR) amplification of HBV DNA. Results obtained indicated that immune complexing was not a common occurrence in the groups investigated, while preliminary findings in patients with isolated anti-HBc positivity demonstrated a 6.5% low level HBV carrier rate in this group
A dissertation submitted to the Faculty of Medicine, University of the Witwatersrand, in partial fulfilment of the requirements for the degree Master of Medicine (Virology)
Keywords: Hepatitis B virus; Serology; In Vitro Techniques